A criação de selos sociais como um mecanismo alternativo para o combate do trabalho escravo contemporâneo na cadeia produtiva da carne bovina mato-grossense - Cançado, Fernanda Brandão (2020)
The aim of this research is to bring about an alternative mechanism to fight contemporary slave labor existing in the Mato Grosso beef production chain, that is, a social label. Current national mechanisms could not eliminate the use of slave-like labor in the Mato Grosso beef production chain, therefore it is proposed to investigate the contribution of the use of social labels as an instrument of combating such practice. Focusing on the requirement of assurances of verification that labor rights are being respected, especially in the early stages of beef production, the aim is to advance the discussion related to the regulatory role that social labels have played in society as a way of achieving global social justice. We use basic and pure theoretical and practical research, qualitative approach, explanatory and exploratory objectives, bibliographic and documentary procedures of doctrine and jurisprudence, case study of labels already applied in the world beef production chain and deductive and hypothetical-deductive reasoning. It was found that the quality control of working conditions in the raising of livestock is within the reach of public authorities and members of the respective beef production chain, but it faces challenges especially related to the lack of mandatory tracking. The provisions of the art. 149 of the Brazilian Penal Code can be used as minimum parameters of reference for the certification about the compliance for the working conditions in the Mato Grosso beef production chain, so that the use of these standards would prevent the unfair national competition; increase the transparency, minimizing the asymmetry of information among consumers; and would contribute to the compliance for decent working conditions throughout the Mato Grosso beef production chain. Despite the non-mandatory nature of the measure, it is advisable for the State of Mato Grosso to encourage the use of this social label as a way of fulfilling a duty the state has to fight contemporary slave labor.